INTERNATIONAL IMPROVING THE STUDENTS LISTENING COMPREHENSION BY USING SPOTIFY APP IN ENGLISH SONG - Zahria Amalina; Rosdiana Rosdiana; Intan Kemala Sari; Hestika Dewi (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
The objectives of this study were to determine whether the use of the Spotify app improves students' listening skills. A pre-experimental design was used in this research. The subjects were 35 tenth-grade students of SMAN 5 Banda Aceh. The researcher conducted a pre-test before the treatment and a post-test to assess the results of the treatment. These tests were used as instruments for data collection. Furthermore, the data were analyzed and interpreted using quantitative procedures with SPSS version 25. The results indicate that the mean score of the post-test is higher than the mean score of the pre-test: the mean score of the post-test was 82.86, while the mean score of the pre-test was 62.43. This shows a difference in students' listening comprehension of English songs and narrative podcasts before and after being taught using the Spotify application. Additionally, based on the statistical analysis using a T-test with SPSS version 25 for Windows, the result of Thitung was -12.116, which is higher than the Ttable value of 1.995469 (-12.116 > 1.995469). This indicates that there is a significant difference in listening comprehension scores before and after being taught with the Spotify application at SMAN 5 Banda Aceh. In conclusion, based on the results, the Spotify application is an effective tool for teaching listening comprehension to students at SMAN 5 Banda Aceh.